Purification of Body and Soul for the Next Journey. Practices Surrounding Death and Dying Among Muslim Women. (December 2017) - Ahaddour, Chaïma; Van den Branden, Stef; Broeckaert, Bert
This study aims, first, to compare normative Islamic practices toward death and dying and actual practices of Moroccan Muslim women. Second, it seeks to compare the views and practices of middle-aged and elderly women. Qualitative empirical research was conducted with 30 middle-aged and elderly Moroccan Muslim women living in Antwerp (Belgium) and with 15 experts in the field. Our study shows that religious beliefs and worldview have a great impact on Muslims' practices surrounding death and dying. More specifically, practices are strongly shaped by their eschatological beliefs. The rituals are perceived as preparations for the hereafter, entailing purification of both soul and body, and demonstrate the belief in a continued existence of the soul. We found striking similarities between our participants' views and normative Islamic views. We did not find a more secular understanding of death and dying among the middle-aged women.